Representasi Mitos dan Ideologi Perempuan dalam Film Televisi Suara Hati Istri - Sunaryanto, Sunaryanto (Gandiwa Jurnal Komunikasi, 2023)
The presence of media in various forms ranging from television to social media in the internet era cannot completely change the position of women who are stereotyped in a bad way. For example, women in the household are represented in the media as a group that is weak, powerless, and unable to determine their own future. This research uses qualitative research with a critical paradigm which is part of media studies and cultural studies. The data collection method was carried out by observing the text of the FTV Voice of the Wife's Heart "The Hardness of Being a Wife Under the Shadow of Her Husband's Family." The data analysis method uses mass media text analysis, namely Roland Barthes' semiotics and Gill Branston and Roy Stafford's theories of questions and representation. This research concludes that FTV Voice of the Wife's Heart, represents the culture that has long been ingrained that a wife should not be better than her husband. A successful wife. The meaning of the myth is that a wife will not be successful and successful without the support of a husband. As a family leader, a husband must be smarter and more successful than his wife. The ideology that is built is the domination of patriarchal power over women. This patriarchal ideology absolutely recognizes that a husband is the leader of his wife. The power of this patriarchal ideology restricts women's freedom to be able to build a business or have a career in the public sphere because wives are only considered to be working in the domestic sphere.